Transcatheter Mitral Valve Repair Effective and Safe for Refractory Eclipsed Mitral Regurgitation-Induced Cardiogenic Shock: A Case Report. (July 2021) - Umei, Tomohiko C.; Shiraishi, Yasuyuki; Tsuruta, Hikaru; Hayashida, Kentaro; Imaeda, Shohei; Ryuzaki, Toshinobu; Myojin, Sosuke; Kobari, Yusuke; Saito, Tetsuya; Yoshijima, Nobuhiro; Itabashi, Yuji; Kishino, Yoshikazu; et al.
Abstract : Supplemental Digital Content is available in the text.